A comprehensive study on composite risers: Material solution, local end fitting design and global response. (September 2018) - Toh, William; Tan, Long Bin; Jaiman, Rajeev K.; Tay, Tong Earn; Tan, Vincent Beng Chye
Abstract: Two up-to-date composite riser solutions, specifically, the thermoset and thermoplastic based ones are studied in a global-local framework to examine their technical feasibility for offshore applications. At the local scale, the riser pipe body with multi-layered structure is homogenized through an analytical approach, obtaining equivalent material properties of the riser string model for the global analysis. The metal-composite interface (MCI) end fittings between the riser body and standard connector are examined using finite element (FE) simulations to understand their load-transfer mechanisms for both solutions. At the global scale, an in-house analysis code is performed to study the risers' static and dynamic response in a certain sea condition due to top-tension, current drag and vortex induced vibration (VIV). The analyzed parameters include the resulting riser deflection, axial stress, tension and bending moment distributions. Following that, an integrated analysis utilizing the global results and the local failure envelopes is performed to determine if the maximum stress states of the riser exceed the equivalent structural strength boundary. It is concluded that composite risers exhibit a larger safety margin than traditional steel riser under the same sea condition. Highlights: Thermoset composite risers do not exhibit clear advantages over steel risers due to the presence of metallic liners. Thermoplastic composite risers can possess significant advantages over steel risers with appropriate design and fabrication. Magna end fitting is superior to trap-lock end fitting designs due to weight-savings and ease of maintenance. More axial plies are recommended for the riser closer to the water surface due to the larger tension experienced.